Severe central nervous and respiratory system depression after sedation with chloral hydrate: a case report - Ceçen, Emre; Uygur, Ozgün; Tosun, Ayşe (The Turkish Journal of Pediatrics, 2009)
Chloral hydrate is generally considered a safe sedative-hypnotic drug, and is commonly used for sedation of infants and young children before diagnostic procedures. Even chloral hydrate administered within the recommended maximal dose limits can cause serious morbidity and mortality. Here the authors describe a four-month-old girl with a life-threatening central nervous system and respiratory depression after administration of a therapeutic dose of chloral hydrate. The patient gradually recovered with supportive treatment including ventilation therapy.